PENYIMPANGAN POLA FONOLOGIS BAHASA INGGRIS SISWA SD TAMPAK SIRING - Dewa Ayu Widiasri (LPPM Universitas Muhammadiyah Sumatera Barat, 2016)
The comprehension of English speech must be entirely based on the ability ofproducing appropriate articulation. This study is simply conducted to find out disoders inEnglish phoneme and supra segmental elements which are produced by students of elementaryschool in Tampak Siring in academic year 2016/2017. The study made use a descriptivequalitative approach. The population of the study were the third, fifth and sixth grade studentsin which 35 of them was taken as sample of the study. The data was collected by using test,questioner and open interview. The collected data was analyzed by interactive analysis. Basedon the result of data analysis, it shows that the whole disorders in articulation of EnglishPhonemes was 532 in total. It consisted of 132 or 23% in fricative, 387 or 72,7 % for inallophones, 4 or 0,75% for in vowel production and 11 or 2,1% for intonation and 7 or 1,3%for stress syllable. Types of disorders were Omission (35,3 %), Addition (6,01 %),Misinformation (51,5 %) and Disordering (7,14 %). The causes of errors wereoovergeneralizations (18 %), Incomplete Applications of Rules (31,01 %), False ConceptsHypothesized (25 %) and Ignore of Rule Restriction (25,37 %). It can be concluded that thestudents have problems in appropriate English articulation. Considering to the significance ofacuracy in expressing spoken message, the teachers must pay deep .attention to this mattersand fix them by encouraging, engaging and envolving them any time practice.Kata kunci: Phonemes, allophones, Phonological process, suprasegmental